An Ullmann CO Coupling Reaction Catalyzed by Magnetic Copper Ferrite Nanoparticles. Issue 1 (12th December 2012) - Yang, Shuliang; Wu, Cunqi; Zhou, Hua; Yang, Yanqin; Zhao, Yongxia; Wang, Chenxu; Yang, Wei; Xu, Jingwei
Abstract Herein, an efficient method for the Ullmann CO coupling reaction between various kinds of phenols and aryl halides, including amino, ketone, cyano, methyl, methoxy, fluoro, chloro and bromo derivatives, is described. The catalyst used, copper ferrite (CuFe2O4) nanoparticles, are easily made, air‐stable, and of low cost. The catalyst can be recycled easily just by using an external magnet. Even in the presence of sensitive substituents, the reaction proceeds successfully to provide the desired products in high yields without protection of other functional groups.